(1-Adamantyl)methyl esters: whole-molecule disorder in the crystal structure of (1-adamantyl)methyl-1-adamantanecarboxylate - Milić, Dalibor (Array, 2009)
Summary:Two (1-adamantyl)methyl esters, (1-adamantyl)methyl-1-adamantanecarboxylate (1) and bis[(1-adamantyl)methyl]-1,3-adamantanedicarboxylate (2) were prepared in good yields and characterized by spectroscopic methods. The structure of 1 was determined by single-crystal X-ray diffraction structural analysis. The structure shows two kinds of whole-molecule disorder: the ester molecule statistically occupies two different sites in the crystal asymmetric unit with occupancies of 95 and 5 % (positional disorder), and at each of the sites there is additional disorder over a crystallographic 2-fold rotation axis (orientational disorder). Analysis of diffuse scattering patterns in the diffraction images revealed the positional disorder as stacking disorder of molecular layers with two-dimensional translational symmetry. In the absence of other, more directional interactions, the molecules in the crystal structure of 1 are held together only by van der Waals interactions which provide the rationale for the observed whole-molecule disorder